Analisis Hubungan Permintaan dan Persediaan Ikan Cakalang (Katsuwonus Pelamis) di Tempat Pelelangan Ikan Sedati Kab. Sidoarjo - Epifanius Oskarino; Didik Trisbiantoro (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
This study aims to analyze the relationship between demand and supply of skipjack tuna at the Fish Auction Place (TPI) Sedati, Sidoarjo Regency. Data were collected through observations, interviews, and literature studies. The research results indicate that fish prices, community income, and supply costs significantly influence the demand and availability of fish at TPI Sedati. Proper stock management is necessary to maintain a balance between demand and supply to improve fishermen's welfare and market efficiency.